الولايات المتحدة الأمريكية والمحكمة الجنائية الدولية (مجلة الواحات للبحوث والدراسات, 2017)
This Article Aims To Study One Of The Most Important Internationale Attitudes Opposed To The Existence Of Internationale Criminal Court, And Affected The Performance Of Its Work, Wich Is The Attitudes Of U.S.A In Order To Clarify How This Stats Country Dealt With The Provision Of The Statute Of The Court, As Wellas The Action Taken By It To Abstruct The Work Of It. Key Words- Withdraw The Signature, American Interpretation Of Article 16 And98